Ecological impacts of photoautotrophic Euendoliths on South African mussel beds - Dievart, Alexia Madeleine Angèle (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Aphytis lingnanensis was reared and tested in South Africa in the early 2000s for augmentation against red scale on citrus and was found to be ineffective. Aphytis melinus is now commercially available and it is important that the efficacy of augmentation thereof on red scale is determined locally. Field trials, fitness assessments and molecular identification on A. melinus from two insectaries were done. Field trials was done in seven, five and six pairs of comparable release and control orchards across the Eastern and Western Cape during the seasons of 2019/2020, 2020/2021 and 2021/2022 respectively. Red scale infestation was monitored and a sample of 20 infested fruit from each orchard was randomly collected every four weeks. Aphytis spp. responsible for parasitism were identified and the percentage parasitism recorded. Results of this study of field trials suggest that the augmentation of A. melinus did not significantly increase the level of parasitism above that of the untreated control. Five repetitions with six replicates of flight and longevity tests were performed with wasps from each insectary. Wasps in the longevity test from two insectaries were kept at 23 Â°C and 65% RH with honey. Flight tests were performed in tubes of 16 by 30 cm, with a light above a clear, sticky ceiling at 23 Â°C and 65% RH. On average in five replicates, 65%, 33% and 17% A. melinus wasps were alive on day one, five and 10 respectively. The overall sex ratio was 1.58 for females to males, but 1.05, 2.19 and 2.66 for non-flyers, non-crawlers, crawlers, and flyers respectively. In flight tests for both insectaries combined, only 36.97% of wasps could initiate flight in 24 h while 56.96% remained on the tube floor, and 6.05% attempted to crawl upwards. No significant differences in flight performance were recorded between the two insectaries. Wasps from the local insectary lived significantly longer during the longevity tests but were shorter in transit than wasps from the overseas insectary. COI genes were sequenced and compared against Genbank sequences using BLAST. Molecular identifications did not confirm morphological identifications for all species, indicating unexpected genetic complexity.
Keywords: Mexilhao mussel; Polychaeta; Epibiosis; Infauna; Infrared thermography; Thermography; Common garden experiment